Pattern and Learning Design of Islamic Religious Education for Early Children - Soni Samsu Rizal; N Hani Herlina; Ahmad Nabil Atoillah; Indahilma Mubarokah (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study examines the learning patterns and designs of Islamic Religious Education (PAI) for Early Childhood Kindergartens (TK) in the City of Ciamis, Indonesia by analyzing learning activities, both in terms of curriculum and teaching materials as well as planning and evaluation systems. Researchers used a descriptive analytical approach to field studies and examined various literature relating to PAI learning for early childhood as a theoretical reference for this research. School document reviews, field observations, interviews with kindergarten heads and teachers are an integral part of this analysis process. This work concludes that kindergarten teachers understand the PAI curriculum and have skills in designing lesson plans even though the implementation process is sometimes not relevant to the Daily Activity Units (SKH) and Weekly Activity Units (SKM) that have been designed. Furthermore, the PAI learning evaluation system is carried out on a daily and semiannual basis, the results of which are both indicators of achieving student progress. All of this illustrates that the implementation of PAI learning in kindergarten has been running adequately to encourage the achievement of educational goals listed in the curriculum, but innovation and creativity are still needed by school principals and teachers so that the learning process is richer and in line with scientific developments and the dynamics of the times.